2016
DOI: 10.1080/09638288.2016.1196399
|View full text |Cite
|
Sign up to set email alerts
|

Selecting relevant and feasible measurement instruments for the revised Dutch clinical practice guideline for physical therapy in patients after stroke

Abstract: Purpose: To select relevant and feasible instruments for the revision of the Dutch clinical practice guideline for physical therapy in patients with stroke. Methods: In this implementation study a comprehensive proposal for ICF categories and matching instruments was developed, based on reliability and validity. Relevant instruments were then selected in a consensus round by 11 knowledge brokers who were responsible for the implementation of the selected instruments. The feasibility of the selected instruments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…recommended specific measures of body function and structures, activity and participation (14, 15, 17, 18, 21, 22). Seven recommended global scales but gave no specific measures for the upper limb (23–28).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…recommended specific measures of body function and structures, activity and participation (14, 15, 17, 18, 21, 22). Seven recommended global scales but gave no specific measures for the upper limb (23–28).…”
Section: Resultsmentioning
confidence: 99%
“…Nine publications referred to the importance of global or upper limb assessments being conducted by appropriately trained or qualified healthcare professionals (HCP) (22, 29–36). Protocols for and timing of assessment was only included in four records (17, 21, 22, 37). In total, reviews identified 47 different global and upper limb specific OMs, but only one referred to effectiveness, validity or reliability of the recommended measures (17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys from Denmark (Maribo et al, 2016) and the United Kingdom (Burton et al, 2013) found that health care professionals used 89 and 81 different assessment tools in stroke rehabilitation, respectively. Occupational therapists may not use a core set of outcome measures in stroke rehabilitation because of a lack of time to administer and analyze data (Otterman et al, 2017) and resources (e.g., training) (Robertson & Blaga, 2013).…”
Section: Standardized Assessmentsmentioning
confidence: 99%
“…Use of standardized and scienti cally sound outcome measures is highly encouraged in clinical practice and research. A number of guidelines have been developed around use of upper extremity outcome measures in stroke [1,2]. However researchers have identi ed that with the development of newer rehabilitation therapies we need technology-supported upper extremity outcome measures that are easily accessible and can measure change consistently and reliably [3].…”
Section: Introductionmentioning
confidence: 99%